Transparência pública: análise das licitações e contratos administrativos realizados na SUDAM - 2015 a 2022 - ALMEIDA, Marcos Rodrigues de (Universidade Federal do Pará, 2023)
The Public Administration has a duty to publicize its purchases, especially with the advent of Law nº 12.527/2011, the so-called Access to Information Law (LAI), which established as public governance guidelines the use of advertising as a general precept. in compliance with legal provisions relating to transparency practices in its bidding processes and in the management of its purchases and contracts. The entities that make up the structure of the Brazilian public administration are required by the Federal Constitution to account for the use of public resources and to respect the principle of publicity, among other principles of public administration. In this way, the path of good governance permeates, among other principles, the transparency of the accounts of public entities and their component bodies in direct and indirect administration. This theme has received greater prominence in recent laws, such as the Fiscal Responsibility Law (LRF), of May 4, 2000, Complementary Law 131/2009 - Transparency Law - and Law No. 12.527/2011 - Access to Information Law (LAI). Considering that SUDAM is in this context of a government agent that has an obligation to provide transparency in its purchases, this work is based on proving good public governance, with regard to active transparency of bids and contracts in the period from 2015 to 2022. Thus, the following problem was formulated to be addressed and contextualized: How can SUDAM demonstrate the level of active transparency in its contracts carried out in the period from 2015 to 2022? Based on a bibliographical and documentary exploration, the proposed methodological scope is divided into two parts. In the first, the application of an indicator capable of measuring the levels of transparency in the acquisition and contracting process in public administration was presented; and the second presented an indicator that proposed to measure the levels of transparency in the publicity process in public acquisitions and contracting.